Collecting qualitative data during a pandemic. (28th October 2021) - Silverman, David
Abstract : I think it is fair to say that the thoughtful comments on my paper were less 'rejoinders' than additions and elaborations. In that spirit, what follows is a summary of the arguments made and the critical questions that remain, also drawing on some personal communications I have received.